Remarks, More Remarks and a Grounds of Decision: One Judgment too Many? TT Durai v Public Prosecutor, Unreported Magistrate's Appeal - MOHAN, S. Chandra (Institutional Knowledge at Singapore Management University, 2009)
In May 2008, the High Court dismissed the appeal of former NKF CEO, T T Durai, against his conviction and sentence. What is little known is that one of Durai's six grounds of appeal was in fact upheld. The appellate judge subsequently devoted nine out of 12 paragraphs of his four-page Grounds of Decision, to explain is reasons for doing so. Although this ruling did not affect the final outcome of the Durai appeal, it has to some extent helped to settle a question that has vexed criminal law practitioners in recent years. This concerns the legality and propriety of writing multiple judgments in a case. Such a practice amongst subordinate court judges was revealed in the Durai case to be more widespread than was previously thought. This note discusses the usefulness of the decision in the light of the uncertainty amongst lower court judges as to the legality of this strange practice. It also examines the shortcomings of the judgment in this regard.